Grammatical performance in children with dyslexia: the contributions of individual differences in phonological memory and statistical learning. (8th May 2021) - van Witteloostuijn, Merel; Boersma, Paul; Wijnen, Frank; Rispens, Judith
Abstract: Several studies have signaled grammatical difficulties in individuals with developmental dyslexia. These difficulties may stem from a phonological deficit, but may alternatively be explained through a domain-general deficit in statistical learning. This study investigates grammar in children with and without dyslexia, and whether phonological memory and/or statistical learning ability contribute to individual differences in grammatical performance. We administered the CELF "word structure" and "recalling sentences" subtests and measures of phonological memory (digit span, nonword repetition) and statistical learning (serial reaction time, nonadjacent dependency learning) among 8- to 11-year-old children with and without dyslexia ( N = 50 per group). Consistent with previous findings, our results show subtle difficulties in grammar, as children with dyslexia achieved lower scores on the CELF (word structure: p = .0027, recalling sentences: p = .053). While the two phonological memory measures were found to contribute to individual differences in grammatical performance, no evidence for a relationship with statistical learning was found. An error analysis revealed errors in irregular morphology (e.g., plural and past tense), suggesting problems with lexical retrieval. These findings are discussed in light of theoretical accounts of the underlying deficit in dyslexia.